Die donker Soutpansberg (vervolg) : Generaal Piet Joubert terug van die buiteland (Historia, 2021)
-
Keywords: Mphefu; Malaboch; Soutpansberg; General Piet Joubert; Joubert; Piet; MaPiet; Makhado; Magoeba; Modjadji